A comparison of the subsecond dynamics of neurotransmission of dopamine and serotonin. - Jennings, K (2013)
The neuromodulators dopamine (DA) and serotonin (5-hydroxytryptamine; 5-HT) are similar in a number of ways. Both monoamines can act by volume transmission at metabotropic receptors to modulate synaptic transmission in brain circuits. Presynaptic regulation of 5-HT and DA is governed by parallel processes, and behaviorally, both exert control over emotional processing. However, differences are also apparent: more than twice as many 5-HT receptor subtypes mediate postsynaptic effects than DA receptors and different presynaptic regulation is also emerging. Monoamines are amenable to real-time electrochemical detection using fast scan cyclic voltammetry (FSCV), which allows resolution of the subsecond dynamics of release and reuptake in response to a single action potential. This approach has greatly enriched understanding of DA transmission and has facilitated an integrated view of how DA mediates behavioral control. However, technical challenges are associated with FSCV measurement of 5-HT and understanding of 5-HT transmission at subsecond resolution has not advanced at the same rate. As a result, how the actions of 5-HT at the level of the synapse translate into behavior is poorly understood. Recent technical advances may aid the study of 5-HT in real-time. It is timely, therefore, to compare and contrast what is currently understood of the subsecond characteristics of transmission for DA and 5-HT. In doing so, a number of areas are highlighted as being worthy of exploration for 5-HT.